Recent developments in smart city assessment: A bibliometric and content analysis-based literature review - Hájek, Petr; Youssef, Abdelrahman Taha; Hájková, Veronika (Elsevier Science BV, 2022)
Cities around the world are increasingly competing to upgrade their infrastructure and smartness levels to attract talent, become more effective and sustainable. However, assessing the progress of smart cities is often challenging due to the lack of theoretical foundation and consensus on an assessment methodology. These contradictions can pose major constraints on the development of the smart city concept and its implementation in practice. This paper analyzes a set of 164 articles published between 2010 and 2020 that deal with smart city assessment. The present study aims to identify the most influential research and key research themes, and suggests future research directions in the field of smart city assessment. A bibliometric analysis is used to reveal the most influential articles and their associations. Furthermore, a content analysis is performed to explore recent developments in the field of smart city assessment in terms of research hotspots and research themes. The analysis reveals the existence of 11 research themes and their timelines. The most influential research addresses (1) multiple-criteria decision-based performance measurement frameworks, (2) data connectivity challenges, (3) composite indexes for smart sustainable cities, (4) holistic performance evaluations of smart cities, and (5) the characteristics of indicator sets. Based on these results, current advances in smart city assessment are discussed, and future research directions in this field are suggested.
Nedávný vývoj v oblasti hodnocení chytrých měst: Přehled literatury založený na bibliometrii a obsahové analýze
Keywords: smart city; assessment; framework; bibliometric analysis; content analysis; literature review; smart city; hodnocení; rámec; bibliometrická analýza; obsahová analýza; přehled literatury